2009
DOI: 10.3171/2009.2.spine08578
|View full text |Cite
|
Sign up to set email alerts
|

The regenerative capacity of the notochordal cell: tissue constructs generated in vitro under hypoxic conditions

Abstract: Object The intervertebral disc (IVD) is a highly avascular structure that is occupied by highly specialized cells (nucleus pulposus [NP] cells) that have adapted to survive within an O2 concentration of 2–5%. The object of this study was to investigate the effects of long-term hypoxic and normoxic tissue cultures of nonchondrodystrophic canine notochordal cells—cells that appear to protect the disc NP from degenerative change. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 33 publications
1
28
0
Order By: Relevance
“…We hypothesized that DPCs are able to maintain vitality under oxygen tension and therefore tested their proliferative activities under hypoxia. We found that DPCs, as well as BMSCs, showed significantly higher proliferation rate at an oxygen tension of 3.5%, which mimics the oxygen level within the IVD [30] (Fig. 4A).…”
Section: Activities Of Dpcs Under Oxygen Tensionmentioning
confidence: 51%
“…We hypothesized that DPCs are able to maintain vitality under oxygen tension and therefore tested their proliferative activities under hypoxia. We found that DPCs, as well as BMSCs, showed significantly higher proliferation rate at an oxygen tension of 3.5%, which mimics the oxygen level within the IVD [30] (Fig. 4A).…”
Section: Activities Of Dpcs Under Oxygen Tensionmentioning
confidence: 51%
“…Here, we cultured the cells under normoxic conditions. It is very likely that the current results would be even more pronounced under hypoxic conditions [10]. This should be tested in a further experiment.…”
Section: Discussionmentioning
confidence: 99%
“…They can produce a better aligned ECM under hypoxic conditions [10]. Here, we cultured the cells under normoxic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…29 Gene expression of brachyury and cytokeratin 8 was significantly decreased at all time points in culture compared with NC-rich NP tissue, indicating a loss of notochordal phenotype and potential de-differentiation of NCs in monolayer culture under normoxic conditions. 32 NCs have been shown to thrive in three-dimensional culture under hypoxic conditions, 32 and therefore we cannot exclude that the culture conditions applied may have been a possible confounding factor. Primary NCs (both clusters and single cells) showed active Wnt/b-catenin signaling with nuclear and cytoplasmic b-catenin expression.…”
Section: Early Ivd Degeneration Involves Increased Canonical Wnt Signmentioning
confidence: 99%